Assessment of Biotic Integrity of the Coastal Freshwater Tidal Zone of a Temperate Estuary of South America through Multiple Indicators - Gómez, Nora (2012)
Fil: Gómez, Nora. Instituto de Limnología Dr. Raúl A. Ringuelet (ILPLA). Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina